Analysis of Food Hygiene, Sanitation Hygiene and Safety of Eating Equipment - Winata, Rivaldi Andika; Lemba, Lemba; Rahmadita, Ninda; Fadhillah, Hikmah; Malsyafinanti, Syarfina; Marlenywati, Marlenywati (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This study aims to assess food cleanliness, hygiene sanitation, and the safety of eating utensils in the canteens at Universitas Muhammadiyah Pontianak, specifically those serving buffet-style food. The research uses a quantitative method with a descriptive approach to describe the cleanliness and sanitation conditions in five canteens on campus. Data were collected through direct observations, interviews, and observation forms with canteen staff. The results show that most canteens have good levels of cleanliness and sanitation, with 80% of canteens receiving a